Mobile Social Networking: An Information Grounds Perspective - Counts, Scott (Proceedings of the 41st Hawaii International Conference on System Sciences - 2008, 2008)
Information grounds are places where people exchange information. Here we examine use of a mobile device-based social networking service as an information ground. The service allows users to form groups and send text and photo messages to those groups. We present usage and questionnaire data from 19 people who shared a primary group in this system and who used the system for 16 months on average. Results highlight the types and usefulness of information shared, the role of information shared in everyday life, the way the system fits into participants’ communication and social “ecosystem”, and the ways in which the system functions as an information ground. Usage analyses describe message sending frequency and system participation levels in relation to other factors, such as length of time in the system. Findings are discussed in the context of the seven propositions of the information grounds framework.